Computational Study of Concrete Corbel - Liew, Bi Hong; Koh, Heng Boon (Recent Trends in Civil Engineering and Built Environment, 2022)
Corbel is a precast connection that protrudes perpendicularly from columns to connect beams and columns together. This paper presents the finite element analysis (FEA) of shallow and deep concrete corbels. The shallow reinforced concrete corbels were analysed using strut-and-tie modelling (STM) and design using Eurocode 2. In the FEA, the concrete corbels were modelled as a surface element subjected to an incremental concentrated load. Nonlinear concrete material was assigned to predict the structural behavior of shallow and deep corbels with various shear span to an effective depth ratio. From the FEA, it was found that the most tensile stress concentration is at the top re-entrant corner for both shallow and deep corbels. The crack was started from the re-entrant corner and extended diagonally to the column. A standard design table was developed for the shallow corbel.